Resin composition
By using a combination of graft copolymer and styrene-based copolymer in the resin composition, the problem of poor chemical resistance and impact resistance of existing transparent plastic materials at low temperatures is solved, and high thermal deformation temperature, excellent transparency and processing properties are achieved.
Patent Information
- Application Number
- CN202380057941.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-21
- Filing Date
- 2023-10-17
- Publication Date
- 2025-03-18
AI Technical Summary
Existing transparent plastic materials have poor chemical resistance and impact resistance at low temperatures and insufficient processing performance, which limits their use in large-scale component applications.
A resin composition is provided, including a graft copolymer and a styrene-based copolymer, which consists of a conjugated diene-based polymer, an alkyl (meth)acrylate-based monomer unit and an aromatic vinyl-based monomer unit. The styrene-based copolymer contains an alkyl (meth)acrylate-based monomer unit, an aromatic vinyl-based monomer unit and a maleimide-based monomer unit.
The resin composition has a thermal deformation temperature of 90.0°C or above under a stress of 18.6 kgf, and the haze change amount is less than 2.0, which significantly improves the heat resistance, transparency and processing properties of the material.
Smart Images

Figure BDA0005261994520000191 
Figure BDA0005261994520000211 
Figure BDA0005261994520000221
Abstract
Description
Technical Field
[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS]
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0136322 filed on October 21, 2022, the entire contents of which are incorporated into this specification by reference.
[0003] The present invention relates to a resin composition. Background Art
[0004] Acrylonitrile-butadiene-styrene (ABS) copolymers are prepared by graft copolymerization of styrene and acrylonitrile to butadiene rubber polymers. ABS copolymers have all the rigidity, chemical resistance and processing properties, as well as excellent impact strength and secondary processing properties such as mechanical properties, surface gloss, plating, printing, coating, etc., and have the advantage of producing products with various colors. However, the use of ABS itself is limited to parts of automotive interior or exterior materials that require heat resistance, or parts that require transparency, such as transparent windows of washing machines, dust cups of vacuum cleaners, and transparent windows of office equipment.
[0005] In order to overcome the defects, a method for providing a transparent plastic material is known. First, a method using a polycarbonate resin as a transparent plastic material is known. Polycarbonate resin has excellent transparency and impact resistance at room temperature, but has poor chemical resistance and impact resistance at low temperatures and insufficient processing performance, and has limitations in application to large parts. In addition, U.S. Patent No. 3,787,522 and Japanese Registered Patent No. 1988-042940 disclose methods for providing a transparent polymethyl methacrylate resin with impact resistance. Polymethyl methacrylate resin has excellent transparency and processing performance, but significantly poor impact resistance, and its application in parts requiring impact resistance is limited. In addition, European Registered Patent No. 0,703,252 discloses a method for providing a high-impact polystyrene (HIPS) resin with transparency, but the high-impact polystyrene resin has the defects of poor chemical resistance and scratch resistance.
[0006] Meanwhile, as a method for preparing an ABS copolymer having excellent heat resistance, a method of introducing a monomer having excellent heat resistance into a part of a resin composition containing an ABS copolymer or a method of adding an inorganic material or the like has been developed. As a conventional method for introducing a monomer having excellent heat resistance, a method of adding a maleimide monomer or an α-methylstyrene monomer during polymerization, or a method of blending a heat-resistant styrene resin containing the monomer with an ABS copolymer is known. However, maleimide monomers have the property of a very fast polymerization rate, and may have the defect that the reaction temperature is difficult to control, and the reaction heat is high, and there are limitations in increasing the content of maleimide monomers in the resin. As the content of maleimide monomers in the resin increases, there are defects in compatibility with ABS copolymers and deterioration of impact strength. In addition, α-methylstyrene monomers have a very slow polymerization rate, require a long reaction time, and have the defects of preparing low molecular weight polymers and being prone to thermal decomposition.
[0007] [Prior art literature]
[0008] [Patent Document]
[0009] (Patent Document 1) US 3787522 A
[0010] (Patent Document 2) JP 1988-042940 B2
[0011] (Patent Document 3) EP 0703252 B2 Summary of the invention
[0012] Technical issues
[0013] The present invention aims to solve the above-mentioned defects of the prior art and provide a resin composition with excellent heat resistance, transparency and processing performance.
[0014] Technical Solution
[0015] In order to achieve the above-mentioned object, the present invention provides a resin composition.
[0016] (1) The present invention provides a resin composition, which comprises a graft copolymer and a styrene copolymer, wherein the graft copolymer comprises a conjugated diene polymer, a (meth)acrylate alkyl ester monomer unit and an aromatic vinyl monomer unit, and the styrene copolymer comprises a (meth)acrylate alkyl ester monomer unit, an aromatic vinyl monomer unit and a maleimide monomer unit.
[0017] (2) The present invention provides the resin composition according to (1), wherein the refractive index of the graft copolymer is 1.515 to 1.520.
[0018] (3) The present invention provides the resin composition according to (1) or (2), wherein the weight average molecular weight of the graft copolymer is 90,000 g / mol to 130,000 g / mol.
[0019] (4) The present invention provides the resin composition according to any one of (1) to (3), wherein the molecular weight distribution of the graft copolymer is 2.7 or less.
[0020] (5) The present invention provides the resin composition according to any one of (1) to (4), wherein the grafting rate of the graft copolymer is 44% or more.
[0021] (6) The present invention provides a resin composition according to any one of (1) to (5), wherein the graft copolymer comprises 20% to 70% by weight of a conjugated diene polymer, 25% to 55% by weight of an alkyl (meth)acrylate monomer unit, 1% to 15% by weight of an aromatic vinyl monomer unit and 0% to 5% by weight of a vinyl cyanide monomer unit.
[0022] (7) The present invention provides the resin composition according to any one of (1) to (6), wherein the graft copolymer contains a maleimide-based monomer unit.
[0023] (8) The present invention provides a resin composition according to (7), wherein the graft copolymer comprises 20% to 70% by weight of a conjugated diene polymer, 25% to 55% by weight of an alkyl (meth)acrylate monomer unit, 0.1% to 3% by weight of a maleimide monomer unit, 1% to 15% by weight of the aromatic vinyl monomer unit and 0% to 5% by weight of a vinyl cyanide monomer unit.
[0024] (9) The present invention provides a resin composition according to any one of (1) to (8), wherein the styrene copolymer contains 50% to 90% by weight of (meth)acrylate monomer units, 1% to 20% by weight of aromatic vinyl monomer units, 1% to 20% by weight of maleimide monomer units and 0% to 5% by weight of vinyl cyanide monomer units.
[0025] (10) The present invention provides a resin composition according to any one of (1) to (9), wherein, based on the total amount of the graft copolymer and the styrene copolymer, the resin composition comprises 10 wt % to 40 wt % of a conjugated diene polymer, 40 wt % to 75 wt % of (meth)acrylate monomer units, 5 wt % to 15 wt % of maleimide monomer units, 5 wt % to 15 wt % of aromatic vinyl monomer units and 0 wt % to 5 wt % of vinyl cyanide monomer units.
[0026] (11) The present invention provides a resin composition according to any one of (1) to (10), wherein the heat deformation temperature of the resin composition is 90.0°C or higher when measured by the method of ASTM D648 under a stress of 18.6 kgf using a test specimen with a thickness of 6.4 mm.
[0027] (12) The present invention provides a resin composition according to any one of (1) to (11), wherein the haze change of the resin composition is less than 2.0, and the haze change is obtained by measuring the haze of a sample with a thickness of 3 mm according to the ASTM D1003 method, storing the sample in a low-temperature chamber at -40°C for 12 hours, measuring the haze again, and calculating according to Mathematical Formula 4.
[0028] [Formula 4]
[0029] △Haze = (Haze of sample after low temperature storage) - (Haze of sample before low temperature storage)
[0030] Beneficial Effects
[0031] The resin composition of the present invention has excellent heat resistance, transparency and processability. DETAILED DESCRIPTION
[0032] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.
[0033] It should be understood that the words or terms used in the specification and claims of the present invention should not be understood as the meanings defined in common dictionaries. It will be understood that based on the inventors can appropriately define the meanings of the words to best illustrate the principles of the present invention, the words or terms should be understood to have the same meanings as they are in the technical concept of the present invention.
[0034] The term "monomer unit" used in the present invention may refer to a component or structure derived from a monomer or material itself, and in a specific embodiment, may refer to a repeating unit formed in a polymer through the participation of a monomer injected in the polymerization reaction during the polymerization process of the polymer.
[0035] The term "composition" as used herein includes mixtures comprising materials of the corresponding composition, as well as reaction products and decomposition products formed from the materials of the corresponding composition.
[0036] The present invention provides a resin composition, which may be a transparent resin composition having excellent heat resistance, transparency and processability.
[0037] According to one embodiment of the present invention, the resin composition may include a graft copolymer and a styrene copolymer, wherein the graft copolymer may include a conjugated diene polymer, an alkyl (meth)acrylate monomer unit and an aromatic vinyl monomer unit, and the styrene copolymer may include an alkyl (meth)acrylate monomer unit, an aromatic vinyl monomer unit and a maleimide monomer unit.
[0038] According to one embodiment of the present invention, the resin composition may be a resin composition comprising a graft copolymer dispersed in a styrene copolymer as a matrix resin. Thus, by simultaneously comprising the graft copolymer and the styrene copolymer, while ensuring impact strength due to the graft copolymer, the heat resistance and processing properties of the transparent composition can be improved.
[0039] According to one embodiment of the present invention, the graft copolymer may include a conjugated diene-based polymer, an alkyl (meth)acrylate-based monomer unit, and an aromatic vinyl-based monomer unit.
[0040] According to one embodiment of the present invention, the conjugated diene-based polymer is a polymer including a conjugated diene-based monomer and polymerized conjugated diene-based monomer units, and may be referred to as a rubber.
[0041] According to one embodiment of the present invention, the conjugated diene monomer may include one or more selected from 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, piperylene, 3-butyl-1,3-octadiene, isoprene and 2-phenyl-1,3-butadiene, and more specifically, may include 1,3-butadiene.
[0042] According to one embodiment of the present invention, the conjugated diene polymer comprises a conjugated diene monomer, and can be a conjugated diene copolymer by further comprising a monomer copolymerizable with the conjugated diene monomer. In a specific embodiment, the conjugated diene polymer can be a butadiene polymer, a butadiene-styrene copolymer or a butadiene-acrylonitrile copolymer.
[0043] According to one embodiment of the present invention, the conjugated diene-based polymer may have a conjugated diene-based polymer latex type including a conjugated diene-based polymer prepared by emulsion polymerization, and may be injected when preparing the graft copolymer.
[0044] According to one embodiment of the present invention, the conjugated diene polymer may have an average particle size of 80nm to 400nm measured using a dynamic light scattering method. In a specific embodiment, the average particle size of the conjugated diene polymer may be more than 80nm, more than 100nm, more than 150nm, more than 200nm, or more than 250nm, and less than 400nm, less than 350nm, or less than 300nm.
[0045] According to one embodiment of the present invention, the conjugated diene polymer latex may have a gel content of 60 wt % to 95 wt %. In a specific embodiment, the gel content of the conjugated diene polymer latex may be 60 wt % or more, 65 wt % or more, or 70 wt % or more, and 95 wt % or less, 90 wt % or less, 85 wt % or less, 80 wt % or less, or 75 wt % or less.
[0046] According to one embodiment of the present invention, the conjugated diene-based polymer latex may have a swelling index of 12 to 40.
[0047] According to one embodiment of the present invention, the graft copolymer may include (meth) alkyl acrylate monomer units, maleimide monomer units and aromatic vinyl monomer units grafted to the conjugated diene polymer. Therefore, the graft copolymer may be a core-shell graft copolymer, which includes: a core including the conjugated diene polymer, and a shell including (meth) alkyl acrylate monomer units, maleimide monomer units and aromatic vinyl monomer units grafted to the conjugated diene polymer.
[0048] According to one embodiment of the present invention, the (meth) alkyl acrylate monomer unit is used to provide the graft copolymer transparency and to improve the compatibility with the styrene copolymer, and the (meth) alkyl acrylate monomer used to form the (meth) alkyl acrylate monomer unit can be an (meth) alkyl acrylate monomer of 1 to 12 carbon atoms. Specific examples of the (meth) alkyl acrylate monomer can be selected from methyl (meth) acrylate, ethyl (meth) acrylate, propyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, decyl (meth) acrylate and lauryl (meth) acrylate. One or more, more specifically, can be methyl (meth) acrylate. Here, (meth) acrylate includes both methacrylate and acrylate.
[0049] According to one embodiment of the present invention, the aromatic vinyl monomer unit is used to improve mechanical properties and compatibility with styrene copolymers, and can be one or more selected from styrene, α-methylstyrene, α-ethylstyrene and p-methylstyrene, specifically, styrene.
[0050] According to one embodiment of the present invention, the graft copolymer may further comprise a vinyl cyanide monomer unit grafted to the conjugated diene polymer. The vinyl cyanide monomer unit is used to improve mechanical properties and compatibility with styrene copolymers, and may be one or more selected from acrylonitrile, methacrylonitrile and ethacrylonitrile, specifically, may be acrylonitrile.
[0051] According to one embodiment of the present invention, the graft copolymer may have a refractive index of 1.515 to 1.520. In a specific embodiment, the graft copolymer may have a refractive index of more than 1.515, more than 1.516, more than 1.517 or more than 1.518, and less than 1.520, less than 1.519 or less than 1.518. Within this range, the transparency of the resin composition may be significantly excellent. The refractive index can be calculated according to Mathematical Formula 1 by the amount of the component injected when preparing the graft copolymer. In addition, the refractive index may be a refractive index measured using an Abbe refractometer. The refractive index can be controlled according to the components and amounts of the polymer and monomer injected when polymerizing the graft copolymer. Specifically, in order to ensure the transparency of the graft copolymer, it is necessary to control the refractive index of the conjugated diene polymer and the refractive index of all the remaining components to a similar degree, and therefore, the mixing ratio of the monomers may be very important. In one embodiment, the refractive index of the injected polymer and monomer components when preparing the graft copolymer can be about 1.518 for 1,3-butadiene, about 1.49 for methyl methacrylate, about 1.63 for N-phenylmaleimide, about 1.55 for styrene, and about 1.52 for acrylonitrile.
[0052] [Mathematical formula 1]
[0053] Refractive index (RI) = ∑Wti*RIi
[0054] -Wti = weight fraction of each component in the graft copolymer (%)
[0055] -RIi = refractive index of the homopolymer of each component in the graft copolymer
[0056] According to one embodiment of the present invention, the graft copolymer may have a weight average molecular weight of 90,000 g / mol to 130,000 g / mol. The weight average molecular weight of the graft copolymer may be the weight average molecular weight of the shell in the core-shell graft copolymer, and in a specific embodiment, may be the weight average molecular weight of the free polymer containing each monomer unit contained in the shell, which is in a state of not being grafted to the conjugated diene polymer as the core. The weight average molecular weight may be obtained by separating the graft copolymer into a sol and a gel, diluting the sol thus obtained in tetrahydrofuran, and measuring by gel permeation chromatography. In a specific embodiment, the weight average molecular weight of the graft copolymer can be 90,000 g / mol or more, 91,000 g / mol or more, 92,000 g / mol or more, 93,000 g / mol or more, 94,000 g / mol or more, 95,000 g / mol or more, 96,000 g / mol or more, 97,000 g / mol or less, 98,000 g / mol or more, 99,000 g / mol or more, 100,000 g / mol or less, In the present invention, the present invention can be used in an embodiment of the present invention to provide a resin composition having an aqueous solution of at least 1,000 g / mol, a polyol of at least 1,000 g / mol, a polyol of at least 1,010 g / mol, a polyol of at least 1,020 g / mol, a polyol of at least 1,030 g / mol, a polyol of at least 1,040 g / mol, a polyol of at least 1,050 g / mol, a polyol of at least 1,060 g / mol, a polyol of at least 1,070 g / mol, a polyol of at least 1,080 g / mol, a polyol of at least 1,090 g / mol, a polyol of at least 1,120 g / mol, a polyol of at least 1,150 g / mol, a polyol of at least 1
[0057] According to one embodiment of the present invention, the molecular weight distribution of the graft copolymer can be 2.7 or less. Here, the molecular weight distribution is the ratio of the weight average molecular weight to the number average molecular weight, which can refer to "weight average molecular weight (Mw) / number average molecular weight (Mn)". The molecular weight distribution of the graft copolymer can be 2.7 or less, 2.6 or less, 2.5 or less, 2.4 or less, or 2.3 or less, and 1.0 or more, 1.5 or more, 2.0 or more, or 2.1 or more, and within this range, the mechanical properties of the resin composition can be good, and the compatibility with the styrene copolymer can be even more excellent.
[0058] According to one embodiment of the present invention, in the process of graft copolymer polymerization, the weight average molecular weight and molecular weight distribution of the graft copolymer can be controlled by a molecular weight regulator. The molecular weight regulator can be a mercaptan type molecular weight regulator, specifically, one or more selected from 1-butyl mercaptan, n-decyl mercaptan, n-hexyl mercaptan and n-octyl mercaptan, more specifically, n-octyl mercaptan.
[0059] According to one embodiment of the present invention, the grafting rate of the graft copolymer can be 44% or more. The grafting rate of the graft copolymer can be obtained by injecting a certain amount of dried copolymer fragments of the graft copolymer latex into acetone, vibrating for 24 hours using a vibrator (product name: SI-600R, manufacturer: Lab.companion) to dissolve the free graft copolymer, centrifuging for 1 hour at 14,000rpm using a centrifuge, and drying for 2 hours at 140°C using a vacuum dryer (product name: DRV320DB, manufacturer: ADVANTEC) to obtain an insoluble component, and calculating according to mathematical formula 2. In a specific embodiment, the grafting rate of the graft copolymer can be 44% or more, 45% or more, 46% or more, 47% or more, 48% or more, 49% or more, or 50% or more, and 80% or less, 75% or less, or 70% or less, and within this range, the mechanical properties of the resin composition can be good, and the compatibility with styrene copolymers can be even more excellent.
[0060] [Mathematical formula 2]
[0061] Grafting rate (%) = [(Y-(X*R)) / (X*R)]*100
[0062] Y: weight of insoluble components
[0063] X: Weight of injected graft copolymer when insoluble components are obtained
[0064] R: Fraction of the conjugated diene polymer in the injected graft copolymer when the insoluble component is obtained
[0065] According to one embodiment of the present invention, in the graft copolymer, considering the improvement of mechanical properties by the graft copolymer, and improving all of heat resistance, transparency and processing properties, the amount of the conjugated diene polymer and each monomer unit can be controlled. In a specific embodiment, the graft copolymer can include 20% to 70% by weight of the conjugated diene polymer, 25% to 55% by weight of the (meth) alkyl acrylate monomer units, 0.1% to 3% by weight of the maleimide monomer units, 1% to 15% by weight of the aromatic vinyl monomer units and 0% to 5% by weight of the vinyl cyanide monomer units.
[0066] According to one embodiment of the present invention, graft copolymer can comprise 20 wt % to 70 wt % of conjugated diene polymer. In a specific embodiment, graft copolymer can comprise more than 20 wt %, more than 25 wt %, more than 30 wt %, more than 35 wt %, more than 40 wt %, more than 45 wt % or more than 50 wt %, and less than 70 wt %, less than 65 wt %, less than 60 wt %, less than 55 wt % or less than 50 wt % of conjugated diene polymer, and within the scope, while ensuring the impact strength of resin combination, graft polymerization can be carried out smoothly, and mechanical property can be even more excellent.
[0067] According to one embodiment of the present invention, the graft copolymer may include 25% to 55% by weight of (meth) alkyl acrylate monomer units. In a specific embodiment, the graft copolymer may include more than 25% by weight, more than 30% by weight or more than 35% by weight, and less than 55% by weight, less than 50% by weight, less than 45% by weight, less than 40% by weight or less than 35% by weight of (meth) alkyl acrylate monomer units, and within this range, the transparency of the resin composition may be good, the compatibility of the graft copolymer with the styrene copolymer may be good, and the mechanical properties may be excellent.
[0068] According to one embodiment of the present invention, the graft copolymer can include 1% to 15% by weight of aromatic vinyl monomer units. In a specific embodiment, the graft copolymer can include more than 1% by weight, more than 5% by weight, more than 6% by weight, more than 7% by weight, more than 8% by weight, more than 9% by weight or more than 10% by weight, and less than 15% by weight, less than 14% by weight, less than 13% by weight or less than 12% by weight of aromatic vinyl monomer units, and within this range, the transparency of the resin combination can be good, the compatibility of the graft copolymer with the styrene copolymer can be good, and the mechanical properties can be excellent.
[0069] According to one embodiment of the present invention, the graft copolymer may contain 0 to 5 wt% of vinyl cyanide monomer units. In a specific embodiment, the graft copolymer may contain 0.0 wt% or more, 0.1 wt% or more, 0.5 wt% or more, 1 wt% or more, 1.5 wt% or more, or 2.0 wt% or more, and 5.0 wt% or less, 4.5 wt% or less, 4.0 wt% or less, 3.5 wt% or less, 3.0 wt% or less, or 2.5 wt% or less of vinyl cyanide monomer units, and within this range, the transparency and color of the resin composition may be good, the coagulant content according to the deterioration of latex stability may be minimized, the compatibility of the graft copolymer with the styrene copolymer may be good, and the mechanical properties may be excellent.
[0070] According to one embodiment of the present invention, the graft copolymer may include a maleimide monomer unit. The maleimide monomer unit is used to provide the graft copolymer with heat resistance and to improve compatibility with the styrene copolymer. The maleimide monomer used to form the maleimide monomer unit can be one or more selected from the following: N-phenylmaleimide, maleimide, N-methylmaleimide, N-ethylmaleimide, N-propylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-isobutylmaleimide, N-tert-butylmaleimide, N-cyclohexylmaleimide, N-chloromaleimide, N-methylphenylmaleimide, N-bromophenylmaleimide, N-naphthylmaleimide, N-laurylmaleimide, N-hydroxyphenylmaleimide, N-methoxyphenylmaleimide, N-carboxyphenylmaleimide, N-nitrophenylmaleimide and N-benzylmaleimide, specifically, it can be N-phenylmaleimide.
[0071] According to one embodiment of the present invention, if the graft copolymer includes maleimide monomer units, the graft copolymer may include 0.1 wt % to 3 wt % maleimide monomer units. Maleimide monomers have a very fast polymerization rate and a defect that the reaction temperature is very difficult to control, and also have a high reaction heat, and preferably need to control a suitable amount to minimize the coagulant content according to the deterioration of latex stability and prevent the discoloration of the resin composition. In a specific embodiment, the graft copolymer may include more than 0.1 wt %, more than 0.5 wt % or more than 1.0 wt %, and less than 3.0 wt %, less than 2.5 wt % or less than 2.0 wt % maleimide monomer units, and within this range, the heat resistance and transparency of the resin composition can be good, the compatibility of the graft copolymer with the styrene copolymer can be good, and the mechanical properties can be excellent.
[0072] According to one embodiment of the present invention, a styrene copolymer may be a base resin of a resin composition, and according to the name of a conventional base resin, it is referred to as a styrene copolymer in the present invention, but in view of the ratio between monomers described below, an acrylic copolymer may also be referred to as a base resin. The styrene copolymer may be a non-grafted copolymer comprising (meth) alkyl acrylate monomer units, aromatic vinyl monomer units, and maleimide monomer units, and may specifically further comprise vinyl cyanide monomer units as required.
[0073] According to one embodiment of the present invention, the (meth) acrylate alkyl ester monomer units, aromatic vinyl monomer units, maleimide monomer units and vinyl cyanide monomer units of the styrene copolymer can be respectively selected from the above-mentioned (meth) acrylate alkyl ester monomers, aromatic vinyl monomers, maleimide monomers and vinyl cyanide monomers of the graft copolymer, and can be the same as or different from the individual monomers of the graft copolymer.
[0074] According to one embodiment of the present invention, styrene copolymers can have a refractive index of 1.515 to 1.520. In a specific embodiment, styrene copolymers can have a refractive index of more than 1.515, more than 1.516, more than 1.517 or more than 1.518, and less than 1.520, less than 1.519 or less than 1.518, and within this range, the transparency of the resin composition can be particularly good. The refractive index can be calculated according to the amount of the component injected when preparing the styrene copolymer according to Mathematical Formula 5. In addition, the refractive index can be the refractive index measured using an Abbe refractometer. The refractive index can be controlled according to the components and amounts of the polymer and monomer injected when polymerizing the styrene copolymer. In one embodiment, according to the refractive index of the monomer component injected when preparing the styrene copolymer, it can be about 1.49 for methyl methacrylate, about 1.63 for N-phenylmaleimide, about 1.55 for styrene, and about 1.52 for acrylonitrile.
[0075] [Mathematical formula 5]
[0076] Refractive index (RI) = ∑Wti*RIi
[0077] -Wti = weight fraction of each component in the styrene copolymer (%)
[0078] -RIi = refractive index of the homopolymer of each component in the styrenic copolymer
[0079] According to one embodiment of the present invention, styrene copolymer can have the weight average molecular weight of 80,000g / mol to 160,000g / mol.The weight average molecular weight of styrene copolymer can be obtained by diluting in tetrahydrofuran and measuring by gel permeation chromatography.In a specific embodiment, the weight average molecular weight of styrene copolymer can be more than 80,000g / mol, more than 85,000g / mol, more than 90,000g / mol, more than 95,000g / mol or more than 100,000g / mol, and less than 160,000g / mol, less than 155,000g / mol, less than 150,000g / mol or less than 140,000g / mol, and within this range, the mechanical property of resin combination can be good, and can be even more excellent with the compatibility of graft copolymer.
[0080] According to one embodiment of the present invention, in styrene copolymer, considering improving the mechanical properties of resin combination, and improving all of heat resistance, transparency and processing properties, the amount of each monomer unit can be controlled. In a specific embodiment, styrene copolymer can include 50% to 90% by weight of (meth) alkyl acrylate monomer units, 1% to 20% by weight of aromatic vinyl monomer units, 1% to 20% by weight of maleimide monomer units and 0% to 5% by weight of vinyl cyanide monomer units.
[0081] According to one embodiment of the present invention, styrene copolymer can comprise 50 wt % to 90 wt % of (meth) alkyl acrylate monomer units. In a specific embodiment, styrene copolymer can comprise more than 50 wt %, more than 55 wt %, more than 60 wt %, more than 65 wt %, more than 70 wt % or more than 75 wt %, and less than 90 wt %, less than 85 wt % or less than 80 wt % of (meth) alkyl acrylate monomer units, and within the scope, the transparency of resin combination can be good, the compatibility of graft copolymer and styrene copolymer can be good, and mechanical property can be excellent.
[0082] According to one embodiment of the present invention, styrene copolymer can comprise 1 wt % to 20 wt % aromatic vinyl monomer units. In a specific embodiment, styrene copolymer can comprise more than 1 wt %, more than 2 wt %, more than 3 wt %, more than 4 wt %, more than 5 wt % or more than 9 wt %, and less than 20 wt %, less than 19 wt %, less than 18 wt %, less than 17 wt %, less than 16 wt % or less than 15 wt % aromatic vinyl monomer units, and within the scope, the transparency of resin combination can be good, the compatibility of graft copolymer and styrene copolymer can be good, and mechanical property can be excellent.
[0083] According to one embodiment of the present invention, styrene copolymer can include 1 wt % to 20 wt % of maleimide monomeric unit. In a specific embodiment, styrene copolymer can include more than 1 wt %, more than 2 wt %, more than 3 wt %, more than 4 wt %, more than 5 wt %, more than 6 wt %, more than 7 wt % or more than 7.5 wt %, and less than 20 wt %, less than 19 wt %, less than 18 wt %, less than 17 wt % or less than 15 wt % of maleimide monomeric unit, and within this range, the heat resistance and transparency of resin combination can be good, the compatibility of graft copolymer and styrene copolymer can be good, and mechanical property can be excellent.
[0084] According to one embodiment of the present invention, the styrene copolymer may contain 0 to 5 wt% of vinyl cyanide monomer units. In a specific embodiment, the styrene copolymer may contain 0.0 wt% or more, 0.1 wt% or more, 0.5 wt% or more, 1 wt% or more, 1.5 wt% or more, or 2.0 wt% or more, and 5.0 wt% or less, 4.5 wt% or less, 4.0 wt% or less, 3.5 wt% or less, or 3.0 wt% or less of vinyl cyanide monomer units, and within this range, the transparency and color of the resin composition may be good, the coagulant content according to the deterioration of latex stability may be minimized, the compatibility of the graft copolymer with the styrene copolymer may be good, and the mechanical properties may be excellent.
[0085] According to one embodiment of the present invention, resin combination can comprise 10 wt % to 40 wt % of graft copolymer and 60 wt % to 90 wt % of styrene copolymer. In a specific embodiment, resin combination can comprise more than 10 wt %, more than 15 wt %, more than 20 wt %, more than 25 wt % or more than 30 wt %, and less than 40 wt %, less than 35 wt % or less than 30 wt % of graft copolymer, and can comprise the styrene compound of surplus as the component except graft copolymer.
[0086] According to one embodiment of the present invention, based on the total amount of graft copolymer and styrene copolymer, resin composition can include 10 wt % to 40 wt % of conjugated diene polymer, 40 wt % to 75 wt % of (meth) alkyl acrylate monomer units, 5 wt % to 15 wt % of maleimide monomer units, 5 wt % to 15 wt % of aromatic vinyl monomer units and 0 wt % to 5 wt % of vinyl cyanide monomer units. If graft copolymer and styrene copolymer are mixed and kneaded in resin composition, although graft copolymer and styrene copolymer include monomer units formed by the same type of monomer, their individual distinction is not easy. The content of conjugated diene polymer and each monomer unit does not refer to the content of polymer and monomer units in graft copolymer and styrene copolymer, but refers to the content of polymer and monomer units in the resin composition comprising graft copolymer and styrene copolymer.
[0087] According to one embodiment of the present invention, resin combination can include 10 % by weight to 40 % by weight of conjugated diene polymers. In a specific embodiment, resin combination can include more than 10 % by weight, more than 11 % by weight, more than 12 % by weight, more than 13 % by weight, more than 14 % by weight or more than 15 % by weight, and less than 40 % by weight, less than 35 % by weight, less than 30 % by weight, less than 25 % by weight or less than 20 % by weight of conjugated diene polymers, and within the scope of this, while ensuring the impact strength of resin combination and mechanical properties, transparency and processing properties can be even better.
[0088] According to one embodiment of the present invention, the resin combination may include 40% to 75% by weight of (meth) alkyl acrylate monomer units. In a specific embodiment, the graft copolymer may include more than 40% by weight, more than 45% by weight, more than 50% by weight, more than 55% by weight or more than 60% by weight, and less than 75% by weight, less than 70% by weight or less than 65% by weight of (meth) alkyl acrylate monomer units, and within this range, the transparency and mechanical properties of the resin combination may be even better.
[0089] According to one embodiment of the present invention, resin combination can include 5 wt % to 15 wt % of maleimide monomeric units. In a specific embodiment, resin combination can include more than 5 wt %, more than 6 wt %, more than 7 wt %, more than 8 wt % or more than 9 wt %, and less than 15 wt %, less than 14 wt %, less than 13 wt %, less than 12 wt %, less than 11 wt % or less than 10 wt % of maleimide monomeric units, and within this range, the heat resistance and transparency of resin combination can be good.
[0090] According to one embodiment of the present invention, resin combination can include 5 wt % to 15 wt % aromatic vinyl monomer units. In a specific embodiment, resin combination can include more than 5 wt %, more than 6 wt %, more than 7 wt %, more than 8 wt % or more than 9 wt %, and less than 15 wt %, less than 14 wt %, less than 13 wt %, less than 12 wt %, less than 11 wt % or less than 10 wt % aromatic vinyl monomer units, and within this range, the transparency of resin combination can be good, and mechanical properties can be excellent.
[0091] According to one embodiment of the present invention, the resin composition may include 0% to 5% by weight of vinyl cyanide monomer units. In a specific embodiment, the graft copolymer may include more than 0.0% by weight, more than 0.1% by weight, more than 0.5% by weight, more than 1% by weight, more than 1.5% by weight, or more than 2.0% by weight, and less than 5.0% by weight, less than 4.5% by weight, less than 4.0% by weight, less than 3.5% by weight, less than 3.0% by weight, or less than 2.5% by weight of vinyl cyanide monomer units, and within this range, the transparency and color of the resin composition may be good.
[0092] According to one embodiment of the present invention, the resin composition may have an Izod notched impact strength of 5.0 kgf·cm / cm or more, 5.5 kgf·cm / cm or more, 6.0 kgf·cm / cm or more, 6.5 kgf·cm / cm or more, 7.0 kgf·cm / cm or more, 7.5 kgf·cm / cm or more, 8.0 kgf·cm / cm or more, or 8.5 kgf·cm / cm or more, and 20.0 kgf·cm / cm or less, 18.0 kgf·cm / cm or less, or 15.0 kgf·cm / cm or less, measured at room temperature (23°C) after a notch is prepared on a specimen having a thickness of 1 / 4 inch according to the method of ASTM D256.
[0093] According to one embodiment of the present invention, the resin composition may have a heat deformation temperature of 90.0°C or more, which is measured by the method of ASTM D648 using a specimen having a thickness of 6.4 mm under a stress of 18.6 kgf. In a specific embodiment, the heat deformation temperature of the resin composition may be 90.0°C or more, 91.0°C or more, 92.0°C or more, 93.0°C or more, 94.0°C or more, 95.0°C or more, 95.7°C or more, 96.0°C or more, 97.0°C or more, 98.0°C or more, 99.0°C or more, or 100.0°C or more, and 110.0°C or less, 108.0°C or less, or 105.0°C or less.
[0094] According to one embodiment of the present invention, the resin composition may have a Vicat softening temperature of 100.0°C or more measured by the method of ASTM D1525. In a specific embodiment, the resin composition may have a Vicat softening temperature of 100.0°C or more, 101.0°C or more, 102.0°C or more, 103.0°C or more, 104.0°C or more, 105.0°C or more, 106.0°C or more, 106.3°C or more, 107.0°C or more, 108.0°C or more, 109.0°C or more, or 110.0°C or more, and 120.0°C or less, 118.0°C or less, or 115.0°C or less.
[0095] According to one embodiment of the present invention, the resin composition may have a haze variation of 5.0 or less, which is obtained by measuring the haze of a sample having a thickness of 3 mm according to the method of ASTM D1003, storing the sample in a low-temperature chamber at -40°C for 12 hours, measuring the haze again, and calculating according to Mathematical Formula 4. In a specific embodiment, the resin composition may have a haze variation of 5.0 or less, 4.5 or less, 4.0 or less, 3.5 or less, 3.0 or less, 2.5 or less, 2.0 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, or 1.5 or less, and 0.0 or 0.1 or more.
[0096] [Formula 4]
[0097] △Haze = (Haze of the sample after low-temperature storage) - (the amount of fog of the sample before low-temperature storage)
[0098] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily implement them. However, the present invention can be implemented in various different ways and is not limited to the embodiments explained in this specification.
[0099] Preparation Example
[0100] Preparation Example 1: Preparation of graft copolymer A
[0101] Into a polymerization reactor substituted with nitrogen, 50 parts by weight of a conjugated diene polymer latex (emulsion polymerization, gel content 70% by weight, average particle size of conjugated diene polymer particles 330 nm) based on solid content, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate as an emulsifier, 37 parts by weight of methyl methacrylate, 2 parts by weight of N-phenylmaleimide, 11 parts by weight of styrene, 0.1 part by weight of n-octyl mercaptan, 0.03 part by weight of ethylenediaminetetraacetic acid, 0.1 part by weight of sodium formaldehyde sulfoxylate, 0.0015 part by weight of ferrous sulfide and 0.2 part by weight of tert-butyl hydroperoxide were continuously injected at 65° C. for 3 hours to carry out polymerization reaction. Then, the internal temperature of the reactor was raised to 70° C., aging was carried out for 1 hour and 30 minutes, and the reaction was terminated to obtain a graft copolymer latex containing a graft copolymer. Thereafter, the graft copolymer latex was coagulated with an aqueous sulfuric acid solution, and the coagulated product was washed, dehydrated and dried to obtain a powder phase graft copolymer A. The graft copolymer A thus obtained had a refractive index of 1.518, a weight average molecular weight of 105,000 g / mol, a PDI of 2.1, a grafting rate of 67%, and a coagulated product content of 0.3 wt%.
[0102] Preparation Example 2: Preparation of Graft Copolymer B
[0103] Into a polymerization reactor substituted with nitrogen, 50 parts by weight of a conjugated diene polymer latex (emulsion polymerization, gel content 70% by weight, average particle size of conjugated diene polymer particles 330 nm) based on solid content, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate as an emulsifier, 36 parts by weight of methyl methacrylate, 2 parts by weight of N-phenylmaleimide, 10 parts by weight of styrene, 2 parts by weight of acrylonitrile, 0.1 part by weight of n-octyl mercaptan, 0.03 part by weight of ethylenediaminetetraacetic acid, 0.1 part by weight of sodium formaldehyde sulfoxylate, 0.0015 part by weight of ferrous sulfide and 0.2 part by weight of tert-butyl hydroperoxide were continuously injected at 65° C. for 3 hours to carry out polymerization reaction. Then, the internal temperature of the reactor was raised to 70° C., aging was carried out for 1 hour and 30 minutes, and the reaction was terminated to obtain a graft copolymer latex containing a graft copolymer. Thereafter, the graft copolymer latex was coagulated with an aqueous sulfuric acid solution, and the coagulate was washed, dehydrated and dried to obtain a powder phase graft copolymer B. The graft copolymer B thus obtained had a refractive index of 1.518, a weight average molecular weight of 114,000 g / mol, a PDI of 2.3, a grafting rate of 69%, and a coagulate content of 0.3 wt%.
[0104] Preparation Example 3: Preparation of Graft Copolymer C
[0105] Into a polymerization reactor substituted with nitrogen, 50 parts by weight of a conjugated diene polymer latex (emulsion polymerization, gel content 70% by weight, average particle size of conjugated diene polymer particles 330 nm) based on solid content, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate as an emulsifier, 37 parts by weight of methyl methacrylate, 1 part by weight of N-phenylmaleimide, 12 parts by weight of styrene, 0.1 part by weight of n-octyl mercaptan, 0.03 part by weight of ethylenediaminetetraacetic acid, 0.1 part by weight of sodium formaldehyde sulfoxylate, 0.0015 part by weight of ferrous sulfide and 0.2 part by weight of tert-butyl hydroperoxide were continuously injected at 65° C. for 3 hours to carry out polymerization reaction. Then, the internal temperature of the reactor was raised to 70° C., aging was carried out for 1 hour and 30 minutes, and the reaction was terminated to obtain a graft copolymer latex containing a graft copolymer. Thereafter, the graft copolymer latex was coagulated with an aqueous sulfuric acid solution, and the coagulate was washed, dehydrated and dried to obtain a powder phase graft copolymer C. The graft copolymer C thus obtained had a refractive index of 1.518, a weight average molecular weight of 109,000 g / mol, a PDI of 2.2, a grafting rate of 55%, and a coagulate content of 0.3 wt%.
[0106] Preparation Example 4: Preparation of Graft Copolymer D
[0107] Into a polymerization reactor substituted with nitrogen, 50 parts by weight of a conjugated diene polymer latex (emulsion polymerization, gel content 70% by weight, average particle size of conjugated diene polymer particles 300 nm) based on solid content, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate as an emulsifier, 34 parts by weight of methyl methacrylate, 0.5 part by weight of N-phenylmaleimide, 11.5 parts by weight of styrene, 4 parts by weight of acrylonitrile, 0.1 part by weight of n-octyl mercaptan, 0.03 part by weight of ethylenediaminetetraacetic acid, 0.1 part by weight of sodium formaldehyde sulfoxylate, 0.0015 part by weight of ferrous sulfide and 0.2 part by weight of tert-butyl hydroperoxide were continuously injected at 65° C. for 3 hours to carry out polymerization reaction. Then, the internal temperature of the reactor was raised to 70° C., aging was carried out for 1 hour and 30 minutes, and the reaction was terminated to obtain a graft copolymer latex containing a graft copolymer. Thereafter, the graft copolymer latex was coagulated with an aqueous sulfuric acid solution, and the coagulated product was washed, dehydrated and dried to obtain a powder phase graft copolymer D. The graft copolymer D thus obtained had a refractive index of 1.518, a weight average molecular weight of 102,000 g / mol, a PDI of 2.3, a grafting rate of 50%, and a coagulated product content of 0.1 wt%.
[0108] Preparation Example 5: Preparation of Graft Copolymer E
[0109] Into a polymerization reactor substituted with nitrogen, 50 parts by weight of a conjugated diene polymer latex (emulsion polymerization, gel content 70% by weight, average particle size of conjugated diene polymer particles 300 nm) based on solid content, 100 parts by weight of ion exchange water, 1.0 parts by weight of sodium oleate as an emulsifier, 34 parts by weight of methyl methacrylate, 12 parts by weight of styrene, 4 parts by weight of acrylonitrile, 0.4 parts by weight of tert-dodecyl mercaptan, 0.03 parts by weight of ethylenediaminetetraacetic acid, 0.1 parts by weight of sodium formaldehyde sulfoxylate, 0.0015 parts by weight of ferrous sulfide and 0.2 parts by weight of tert-butyl hydroperoxide were continuously injected at 65° C. for 3 hours to carry out polymerization reaction. Then, the internal temperature of the reactor was raised to 70° C., aging was carried out for 1 hour and 30 minutes, and the reaction was terminated to obtain a graft copolymer latex containing a graft copolymer. Thereafter, the graft copolymer latex was coagulated with a sulfuric acid aqueous solution, the coagulated product was washed, dehydrated and dried to obtain a graft copolymer E in a powder phase. The graft copolymer E thus obtained had a refractive index of 1.518, a weight average molecular weight of 102,000 g / mol, a PDI of 3.3, a grafting rate of 38%, and a coagulant content of 0.2% by weight.
[0110] Preparation Example 6: Preparation of Styrene Copolymer A
[0111] Into a polymerization reactor equipped with a stirrer, 75 parts by weight of methyl methacrylate, 9 parts by weight of styrene, 3 parts by weight of acrylonitrile, 3 parts by weight of N-phenylmaleimide, 64 parts by weight of ion exchange water, 0.02 parts by weight of 1,1-di(tert-butylperoxy)cyclohexane, 0.02 parts by weight of diisopropylbenzene peroxide and 1.3 parts by weight of tricalcium phosphate were injected in batches, the stirring speed of the reactor was set to 500rpm, the temperature of the reactor was raised to 90°C, and polymerization was initiated. Then, from the point where the polymerization conversion rate reached 5% to the point where the polymerization conversion rate reached 60%, 86 parts by weight of ion exchange water were continuously injected into the reactor at a constant rate. In addition, from the point where the polymerization conversion rate reached 5% to the point where the polymerization conversion rate reached 70%, polymerization was carried out while 10 parts by weight of N-phenylmaleimide were continuously injected into the reactor at a constant rate. In this case, the continuous injection of ion exchange water was carried out for 100 minutes, and the continuous injection of N-phenylmaleimide was carried out for 150 minutes. After the continuous injection of ion exchange water and N-phenylmaleimide was completed, polymerization was carried out for 90 minutes while the reactor temperature was maintained at 90° C., polymerization was carried out for 20 minutes while the reactor temperature was raised to 120° C., polymerization was carried out for 100 minutes while the reactor temperature was maintained at 120° C., and then the polymerization was terminated. Formic acid was injected into the thus obtained polymerization slurry to adjust the acid value of the slurry to 2.5, the dispersant was removed, and the resultant was washed, dehydrated and dried to obtain a bead type styrene copolymer A.
[0112] Preparation Example 7: Preparation of Styrene Copolymer B
[0113] Into a polymerization reactor equipped with a stirrer, 79 parts by weight of methyl methacrylate, 4 parts by weight of styrene, 5 parts by weight of N-phenylmaleimide, 64 parts by weight of ion exchange water, 0.02 parts by weight of 1,1-di(tert-butylperoxy)cyclohexane, 0.02 parts by weight of diisopropylbenzene peroxide and 1.3 parts by weight of tricalcium phosphate were injected in batches, the stirring speed of the reactor was set to 500rpm, the temperature of the reactor was raised to 90°C, and polymerization was initiated. Then, from the point where the polymerization conversion rate reached 5% to the point where the polymerization conversion rate reached 60%, 86 parts by weight of ion exchange water were continuously injected into the reactor at a constant rate. In addition, from the point where the polymerization conversion rate reached 5% to the point where the polymerization conversion rate reached 70%, polymerization was carried out while 12 parts by weight of N-phenylmaleimide were continuously injected into the reactor at a constant rate. In this case, the continuous injection of ion exchange water was carried out for 100 minutes, and the continuous injection of N-phenylmaleimide was carried out for 150 minutes. After the continuous injection of ion exchange water and N-phenylmaleimide was completed, polymerization was carried out for 90 minutes while the reactor temperature was maintained at 90° C., polymerization was carried out for 20 minutes while the reactor temperature was raised to 120° C., polymerization was carried out for 100 minutes while the reactor temperature was maintained at 120° C., and then the polymerization was terminated. Formic acid was injected into the thus obtained polymerization slurry to adjust the acid value of the slurry to 2.5, the dispersant was removed, and the resultant was washed, dehydrated and dried to obtain a bead type styrene copolymer B.
[0114] Preparation Example 8: Preparation of Styrene Copolymer C
[0115] Into a polymerization reactor equipped with a stirrer, 75 parts by weight of methyl methacrylate, 17.5 parts by weight of styrene, 2 parts by weight of N-phenylmaleimide, 64 parts by weight of ion exchange water, 0.02 parts by weight of 1,1-di(tert-butylperoxy)cyclohexane, 0.02 parts by weight of diisopropylbenzene peroxide and 1.3 parts by weight of tricalcium phosphate were injected in batches, the stirring speed of the reactor was set to 500rpm, the temperature of the reactor was raised to 90°C, and polymerization was initiated. Then, from the point where the polymerization conversion rate reached 5% to the point where the polymerization conversion rate reached 60%, 86 parts by weight of ion exchange water were continuously injected into the reactor at a constant rate. In addition, from the point where the polymerization conversion rate reached 5% to the point where the polymerization conversion rate reached 70%, polymerization was carried out while 5.5 parts by weight of N-phenylmaleimide were continuously injected into the reactor at a constant rate. In this case, the continuous injection of ion exchange water was carried out for 100 minutes, and the continuous injection of N-phenylmaleimide was carried out for 150 minutes. After the continuous injection of ion exchange water and N-phenylmaleimide was completed, polymerization was carried out for 90 minutes while the reactor temperature was maintained at 90° C., polymerization was carried out for 20 minutes while the reactor temperature was raised to 120° C., polymerization was carried out for 100 minutes while the reactor temperature was maintained at 120° C., and then the polymerization was terminated. Formic acid was injected into the thus obtained polymerization slurry to adjust the acid value of the slurry to 2.5, the dispersant was removed, and the resultant was washed, dehydrated and dried to obtain a bead type styrene copolymer C.
[0116] Preparation Example 9: Preparation of Styrene Copolymer D
[0117] Into a continuous polymerization reactor, a material obtained by mixing 64 parts by weight of methyl methacrylate, 26 parts by weight of styrene, 7 parts by weight of acrylonitrile, 3 parts by weight of methacrylic acid, 30 parts by weight of ethylbenzene and 0.15 parts by weight of tert-dodecyl mercaptan was continuously injected so that the average retention time was 3 hours. In this case, the temperature of the reactor was maintained at 148° C. The polymerization solution continuously discharged from the reactor was heated in a preheating bath, and the unreacted monomers were volatilized in a volatilization bath. While the temperature of the polymerization solution was maintained at 210° C., a granular styrene copolymer D was obtained using a polymer delivery pump extruder.
[0118] Examples and Comparative Examples
[0119] The components were mixed in the amounts shown in Table 1 and extruded using a biaxial extrusion kneader at a cylinder temperature of 250° C. to prepare a pellet-type transparent resin composition.
[0120] In this case, the amounts of the components are based on 100 parts by weight in total of the graft copolymer and the styrene-based copolymer.
[0121] [Table 1]
[0122]
[0123] Experimental example
[0124] Experimental Example 1
[0125] For the graft copolymers A to E prepared in Preparation Examples 1 to 5, the refractive index, weight average molecular weight, molecular weight distribution, grafting ratio and coagulant content were measured by the following methods and are shown in Table 2.
[0126] *Refractive index: calculated according to Mathematical Formula 1 based on the amount of components injected during the preparation of the graft copolymer of each preparation example.
[0127] [Mathematical formula 1]
[0128] Refractive index (RI) = ∑Wti*RIi
[0129] -Wti = weight fraction of each component in the graft copolymer (%)
[0130] -RIi = refractive index of the homopolymer of each component in the graft copolymer
[0131] *Weight average molecular weight and molecular weight distribution: Each graft copolymer fragment prepared in the preparation example was injected into acetone and stirred for 24 hours, and the rubber component (insoluble component) insoluble in acetone and the copolymer component (soluble component) soluble in acetone were separated using a centrifuge. For the separated soluble components in acetone, the weight average molecular weight, number average molecular weight and molecular weight distribution were measured using gel permeation chromatography (GPC). In this case, two PLgel Olexis columns and one PLgel mixed-C column from PolymerLaboratories Co. were used in combination. In addition, the newly replaced columns were all mixed bed type columns, and polystyrene was used as the GPC standard material.
[0132] -Solvent: Tetrahydrofuran (stabilized with BHT)
[0133] -Flow rate: 1.0ml / min
[0134] - Sample concentration: 2.0mg / ml
[0135] -Injection volume: 100μl
[0136] - Column temperature: 30℃
[0137] -Detector: Waters 2414 Refractive Index Detector
[0138] -Data processing: Empower 3
[0139] *Grafting rate (%): A certain amount of dried copolymer fragments of each graft copolymer latex prepared in the preparation example was injected into acetone, vibrated in a vibrator (product name: SI-600R, manufacturer: Lab.companion) for 24 hours to dissolve the free graft copolymer, centrifuged at 14,000 rpm for 1 hour using a centrifuge, and dried at 140°C for 2 hours in a vacuum dryer (product name: DRV320DB, manufacturer: ADVANTEC) to obtain an insoluble component, and calculated according to Mathematical Formula 2.
[0140] [Mathematical formula 2]
[0141] Grafting rate (%) = [(Y-(X*R)) / (X*R)]*100
[0142] Y: weight of insoluble components
[0143] X: Weight of injected graft copolymer when insoluble components are obtained
[0144] R: Fraction of the conjugated diene polymer in the injected graft copolymer when the insoluble component is obtained
[0145] * Coagulant content (wt%): Each graft copolymer latex prepared in the preparation example was sieved through a 100 mesh sieve, the material that did not pass through the sieve was dried in a hot air dryer at 80°C for 6 hours, and the weight of the solid coagulant was measured, and then calculated according to Mathematical Formula 3.
[0146] [Mathematical formula 3]
[0147] Coagulant content (%) = [weight of dried coagulant after separation by mesh screen (g) / total weight of rubber and monomer used for polymerization (g)] x 100
[0148] [Table 2]
[0149]
[0150] Experimental Example 2
[0151] Using the test specimens prepared by injecting the pellets formed in Examples 1 to 6 and Comparative Examples 1 to 4 at an injection temperature of 210° C. using a syringe, impact strength, heat deformation temperature, Vicat softening temperature and low-temperature whitening were measured by the following methods, and the results are shown in Table 3.
[0152] *Impact strength (kgf·cm / cm): According to the method of ASTM D256, a specimen having a thickness of 1 / 4 inch was notched and the Izod notched impact strength was measured at room temperature (23° C.) using an impact strength measuring machine (TINIUS OLSEN Co.).
[0153] *Heat deformation temperature (HDT, °C): measured according to the method of ASTM D648 using a specimen with a thickness of 6.4 mm under a stress of 18.6 kgf.
[0154] * Vicat softening temperature (°C): measured according to the method of ASTM D1525, under the conditions of a load of 50 N, a maximum penetration of 1.0 mm and 50°C / hr, using a specimen having a width of 10 mm and a thickness of 3.2 mm.
[0155] * Low temperature whitening (△ haze): According to the method of ASTM D1003, the haze of a sample with a thickness of 3 mm was measured using a haze meter HZ-V3. Then, the sample was stored in a low temperature chamber at -40°C for 12 hours, the haze was measured again, and the haze change was calculated according to Mathematical Formula 4.
[0156] [Formula 4]
[0157] △Haze = (Haze of sample after low temperature storage) - (Haze of sample before low temperature storage)
[0158] [Table 3]
[0159]
[0160] As shown in Table 3, the resin compositions according to Examples 1 to 6 of the present invention have a molecular weight distribution of less than 2.5 and a high grafting rate, and contain a graft copolymer containing a maleimide monomer unit. It can be confirmed that the compatibility between the graft copolymer and the styrene copolymer as the base resin is excellent, the impact strength is excellent, and the heat resistance and low-temperature whitening are excellent.
[0161] In contrast, although the resin compositions of Comparative Examples 1 to 3 included the same graft copolymer as Examples 1 to 3, it was confirmed that the styrene-based copolymer as the base resin did not include the maleimide-based monomer unit and had significantly poor heat resistance.
[0162] Furthermore, in the resin composition of Comparative Example 4, both the graft copolymer and the styrene-based copolymer did not include a maleimide-based monomer unit, and it was confirmed that heat resistance and low-temperature whitening were poor.
Claims
1. A resin composition comprising: Graft copolymers and styrene copolymers, in, The graft copolymer comprises a conjugated diene polymer, a (meth)acrylic acid alkyl ester monomer unit and an aromatic vinyl monomer unit. The styrene-based copolymer comprises an alkyl (meth)acrylate-based monomer unit, an aromatic vinyl-based monomer unit and a maleimide-based monomer unit.
2. The resin composition according to claim 1, wherein The graft copolymer has a refractive index of 1.515 to 1.
520.
3. The resin composition according to claim 1, wherein The weight average molecular weight of the graft copolymer is 90,000 g / mol to 130,000 g / mol.
4. The resin composition according to claim 1, wherein The molecular weight distribution of the graft copolymer is less than 2.
7.
5. The resin composition according to claim 1, wherein The grafting rate of the graft copolymer is greater than 44%.
6. The resin composition according to claim 1, wherein The graft copolymer comprises: 20 to 70 wt% of a conjugated diene polymer; 25 to 55 wt% of alkyl (meth)acrylate monomer units; 1 to 15 wt% of aromatic vinyl monomer units; and 0 to 5% by weight of vinyl cyanide monomer units.
7. The resin composition according to claim 1, wherein The graft copolymer comprises maleimide monomer units.
8. The resin composition according to claim 7, wherein The graft copolymer comprises: 20 to 70 wt% of a conjugated diene polymer; 25 to 55 wt% of alkyl (meth)acrylate monomer units; 0.1 wt % to 3 wt % of maleimide monomer units; 1 to 15 wt% of aromatic vinyl monomer units; and 0 to 5% by weight of vinyl cyanide monomer units.
9. The resin composition according to claim 1, wherein The styrene copolymer comprises: 50 to 90% by weight of alkyl (meth)acrylate monomer units; 1 to 20% by weight of aromatic vinyl monomer units; 1 to 20 wt% of maleimide monomer units; and 0 to 5% by weight of vinyl cyanide monomer units.
10. The resin composition according to claim 1, wherein Based on the total amount of the graft copolymer and the styrene copolymer, the resin composition comprises: 10 to 40 wt% of a conjugated diene polymer; 40 to 75% by weight of alkyl (meth)acrylate monomer units; 5 to 15 wt% of maleimide monomer units; 5 to 15 wt% of aromatic vinyl monomer units; and 0 to 5% by weight of vinyl cyanide monomer units.
11. The resin composition according to claim 1, wherein The resin composition has a heat deformation temperature of 90.0° C. or more when measured by the method of ASTM D648 using a test specimen having a thickness of 6.4 mm under a stress of 18.6 kgf.
12. The resin composition according to claim 1, wherein The resin composition has a haze variation of 2.0 or less, which is obtained by measuring the haze of a sample having a thickness of 3 mm according to the method of ASTM D1003, storing the sample in a low-temperature chamber at -40°C for 12 hours, measuring the haze again, and calculating according to the following mathematical formula 4: [Formula 4] ΔHaze = (Haze of the sample after low-temperature storage) - (Haze of the sample before low-temperature storage).
Citation Information
Patent Citations
Transparent, rubber-modified styrene resin and production process thereof
EP0703252B2
Wefting control apparatus
JP1988042940A
Handle For Furniture
KR1020220136322A
Acrylate polymer particles comprising a core,an outer shell,and an intermediate layer
US3787522A